A pedagogia libertadora de Paulo Freire, o ensino por investigação e a teoria de aprendizagem sócio-histórica: articulações possíveis para o ensino de química - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This work aimed to show that the teaching of Chemistry in High School can benefit from the contributions of Paulo Freire's Pedagogy of Liberation and Teaching by Inquiry. In order to put in to practice in the classroom the methodological approach built by combining the set wo approaches, we opted for the use of na Investigative Teaching Sequence (SEI) that articulated the set wo ideas in order to contribute to the Scientific Literacy (AC) processof high school students in two public schools in the city of Anápolis - GO. SEI was applied in view of the teacher's mediating posture, based on the learning theory proposed by Vygotsky. Through the analysis of the results, were alized that the attitude of the teacher-researcher Who guided and directed the students' work in each stage of SEI was decisive for the achievement of the proposed objectives. SEI enabled a greater under standing of the concepts of Chemistry related to the polarity and solubility of solutions, in addition to the development of skills related to group work. In addition, two of the three structuring axés of Scientific Literacy were found in the students' productions, namely: basic understanding of fundamental scientific terms, know ledge and concepts and understanding of the relationships between Science, Technology, Society and the Environment, evidencing a principle of AC in the intended process.
The relevant pedagogy of Paulo Freire, research teaching and the socio-historic learning theory: possible joints for teaching chemistry
Keywords: Pedagogia libertadora; Teoria sócio-histórica; Sequência de ensino investigativa; Ensino de química; Ensino médio; Alfabetização científica; Liberating pedagogy; Socio-historical theory; Investigative teaching sequence; Chemistry teaching; High school; Scientific literacy; CIENCIAS EXATAS E DA TERRA::QUIMICA; EDUCACAO::ENSINO-APRENDIZAGEM